The impact of peer feedback on Chinese EFL junior high school students writing performance - Hao, Hongxia; Razali, Abu Bakar (Canadian Center of Science and Education (CCSE), 2022)
English writing plays a vital role in language teaching and learning and is compulsory in Chinese secondary education. Chinese EFL junior high school students need to master English writing. However, in the process of English writing teaching and learning, the Chinese EFL students still face problems in writing ability and self-efficacy even though they receive corrective feedback from teachers. In this regard, the authors believe peer feedback as a formative evaluation method also significantly promotes students' writing performance. So, the purpose of this study is to explore the effectiveness of peer feedback on Chinese EFL junior high school students’ writing ability and self-efficacy. The participants in this study were 100 grade 9 EFL students in a Chinese public junior high school, divided into experimental and control classes. Both teacher feedback and peer feedback were used in the experimental class, while only teacher feedback was used in the control class. Data were collected using the quasi-experimental and survey questionnaire methods, and data were analyzed using SPSS version 23. The findings revealed that peer feedback positively impacts students' writing ability in content, organization, and grammar. Additionally, students have more positive attitudes toward peer feedback which is more conducive to improving the students’ writing self-efficacy in motivation and confidence. Therefore, it can be considered that peer feedback has a positive impact on Chinese EFL junior high school students' writing ability and self-efficacy. The author also proposed the recommendations and implications for EFL writing instruction, policies, and future research.